Lesions of the medial and lateral striatum in the rat produce differential deficits in attentional performance. - Rogers, R; Baunez, C; Everitt, B; Robbins, T (2001)
Excitotoxic lesions of the medial frontal cortex and anterior cingulate cortex in rats have been shown to produce dissociable impairments on a reaction time visual attention (5-choice) task. Because these cortical areas project to the medial striatal region, the authors predicted similar deficits after lesions of this striatal area compared with the lateral area. Compared with sham-operated controls, rats with quinolinic acid-induced medial striatal lesions showed all the behavioral changes associated with medial frontal cortex and anterior cingulate cortex lesions. In contrast, lateral striatal lesions produced profound disturbances in the performance of the task. Control tests showed little evidence of gross deficits in either group of rats in terms of motivation, locomotor function, or Pavlovian appetitive conditioning. These data suggest that the medial and lateral striatum have contrasting roles in the control of instrumental responding related to the primary sources of their cortical innervation.